Design, synthesis, and evaluation of 1,4-benzothiazine-3-one containing bisamide derivatives as dual inhibitors of Staphylococcus aureus with plausible application in a urinary catheter - Naithani, Kaushal; Das, Arka; Ushare, Mamta; Nath, Subham; Biswas, Rashmita; Kundu, Anirban; Ahmed, Kazi Tawsif; Mohan, Utpal; Bhowmik, Subhendu (Frontiers in Chemistry, 2024)
In this study, 1,4-benzothiazine-based bisamide derivatives, a new class of antibacterial agents targeting bacterial peptide deformylase (PDF), were designed and synthesized to combat Staphylococcus aureus infection. Molecular modeling of the designed molecules showed better docking scores compared to the natural product actinonin. Bioactivity assessment identified two derivatives with promising antibacterial activity in vitro. The stability of the most active molecule, 8bE, was assessed using molecular dynamics (MD) simulation. Significantly, compound 8bE could also inhibit the S. aureus biofilm at low concentrations. Furthermore, the capability of the synthesized molecule to inhibit S. aureus biofilm formation on medical devices like urinary catheters is also demonstrated.